Analisis Laporan Keuangan dalam Mengukur Kinerja Keuangan BAZNAS Provinsi Papua - Taufik Maulid; Syaikhul Falah; Hesty Theresia Salle (Politeknik Negeri Jember, 2022)
This study aims to determine the financial performance of the Automotive Sector Manufacturing companies for the 2018-2020 period. The data used in this study is secondary data obtained indirectly from the results of the company's financial statements. This type of research is descriptive research. The data analysis technique in this study used descriptive statistics to view and analyze the existing data. The results showed that the financial performance of the companies studied showed that they were in the unhealthy category because the average value produced was less than the industry standard which has been set.